2010
DOI: 10.1007/s00270-010-9863-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Hemostatic Durability between N-Butyl Cyanoacrylate and Gelatin Sponge Particles in Transcatheter Arterial Embolization for Acute Arterial Hemorrhage in a Coagulopathic Condition in a Swine Model

Abstract: This study was designed to compare the efficacy of transcatheter arterial embolization (TAE) with N-butyl cyanoacrylate (NBCA) or gelatin sponge particles (GSP) for acute arterial bleeding in a coagulopathic condition using a swine model. Four healthy swine were divided into two coagulopathic conditions: mild and severe. Five hemorrhages were created in each swine (10 hemorrhages per coagulopathy). Mild coagulopathy was achieved by bloodletting 10% of the total circulatory whole blood and preserving activated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 18 publications
1
37
0
Order By: Relevance
“…In addition, the operations were completed more quickly in the NBCA group (9 min ± 4) than in the microcoils group (37 min ± 19) or the gelatin sponge particle group (25 min ± 10) [185]. In a swine model-based experimental study comparing the hemostatic durability achieved by NBCA and gelatin sponge particles during transcatheter arterial embolization for acute arterial hemorrhaging in coagulopathic conditions (activated clotting time [ 400 s), follow-up angiography performed after the embolization procedure detected recurrent hemorrhaging in four (80 %) of the five hemorrhages that had been embolized with gelatin sponge particles, but only one (20 %) of the five hemorrhages that were embolized with NBCA [186].…”
Section: International Situationmentioning
confidence: 99%
“…In addition, the operations were completed more quickly in the NBCA group (9 min ± 4) than in the microcoils group (37 min ± 19) or the gelatin sponge particle group (25 min ± 10) [185]. In a swine model-based experimental study comparing the hemostatic durability achieved by NBCA and gelatin sponge particles during transcatheter arterial embolization for acute arterial hemorrhaging in coagulopathic conditions (activated clotting time [ 400 s), follow-up angiography performed after the embolization procedure detected recurrent hemorrhaging in four (80 %) of the five hemorrhages that had been embolized with gelatin sponge particles, but only one (20 %) of the five hemorrhages that were embolized with NBCA [186].…”
Section: International Situationmentioning
confidence: 99%
“…NBCA is highly penetrable because of its liquid nature and is less affected by coagulopathies; thus, it may be used as an adjunct to other embolic materials to ensure the embolic effect [9,10]. However, NBCA is difficult to handle effectively and safely and is inherently more prone to cause ischemic necrosis.…”
mentioning
confidence: 99%
“…The most common embolization materials were microcoils (ten patients, 40%), particles (seven patients, 28%), NBCA (six patients, 24%), and microcoils and particles (two patients, 8%). In patients receiving antiplatelet therapy or exhibiting a coagulopathic condition, it is most important to select the embolic materials for the control of acute hemorrhage 15,16 . Yonemitsu et al 15 reported the outcome of transcatheter arterial embolization with GSPs, microcoils, and NBCA for controlling acute arterial bleeding in a coagulopathic condition.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular embolization enables treatment via selective embolization and the achievement of adequate hemostasis in a coagulopathic condition or during antiplatelet therapy 15,16 .…”
Section: Introductionmentioning
confidence: 99%